2023
DOI: 10.3390/su151914398
|View full text |Cite
|
Sign up to set email alerts
|

Revolutionizing Agriculture: Leveraging Hydroponic Greenhouse Wastewater for Sustainable Microalgae-Based Biostimulant Production

María Álvarez-Gil,
Mario Blanco-Vieites,
David Suárez-Montes
et al.

Abstract: The current intensification in agricultural pressure has resulted in the addition of excessive amounts of nutrients. While hydroponic systems have become an agricultural tool to reduce this nutrient addition, the produced nutrient-rich drainage solution, which has a negative effect in water bodies, is still a barrier that needs to be overcome. A promising alternative for nutrient recovery is the cultivation of microalgae, which require a significant quantity of nutrients for their growth. Furthermore, their bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Both studies underscore the potential of enzyme treatments in altering chlorophyll concentration and cell wall structure, with implications for various applications in biotechnology and agriculture. The current study's findings align with those of Álvarez et al [17], who found that a 10% concentration of the "EnzMix" complex is optimal for efficient degradation of cell walls. This suggests consistency in the efficacy of the enzyme complex across different research investigations, reinforcing its potential as a reliable tool for cell wall degradation processes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Both studies underscore the potential of enzyme treatments in altering chlorophyll concentration and cell wall structure, with implications for various applications in biotechnology and agriculture. The current study's findings align with those of Álvarez et al [17], who found that a 10% concentration of the "EnzMix" complex is optimal for efficient degradation of cell walls. This suggests consistency in the efficacy of the enzyme complex across different research investigations, reinforcing its potential as a reliable tool for cell wall degradation processes.…”
Section: Discussionsupporting
confidence: 91%
“…strain. This microalgae species was selected based in previous studies [17]. Illustration of the biostimulant production process.…”
Section: Working Phases and Algae Growth Cyclesmentioning
confidence: 99%
“…Due to the significant concentrations of phosphates and nitrates released into the environment, GW can contribute to the eutrophication of local water reservoirs and also pollute groundwater [ 8 ]. Discharging GW into the sewage system is also not an optimal solution.…”
Section: Introductionmentioning
confidence: 99%